KONEKTIFITAS IDE, PERILAKU DAN ARTEFAK DALAM A DOLL’S HOUSE KARYA HENRIK IBSEN - EMAN, KARLITA MARSHA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
Abstract The problems of this research is how does Ibsen connect the idea, behavior and material culture in A Doll’s House, and the objective of this research is to recognize the ways Ibsen connect the idea, behavior, and material culture in A Doll’s House. Then the writer using three steps in terms of methodology. They are preparation, data collection and analysis.